2021
DOI: 10.48550/arxiv.2103.00879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DR-TANet: Dynamic Receptive Temporal Attention Network for Street Scene Change Detection

Abstract: Street scene change detection continues to capture researchers' interests in the computer vision community. It aims to identify the changed regions of the paired street-view images captured at different times. The state-of-the-art network based on the encoder-decoder architecture leverages the feature maps at the corresponding level between two channels to gain sufficient information of changes. Still, the efficiency of feature extraction, feature correlation calculation, even the whole network requires furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Recently, several studies have reported the effectiveness of attention in change detection tasks. HPCFNet [28] represents attention as a correlation between feature maps, DR-TA Net [15] evaluates temporal attention by computing the similarity and dependency between a feature map pair, to realize attention-based change detection. CSCDNet [11] employs a correlation filter to compensate for the uncertainty in the nonlinear transformation between live and reference images.…”
Section: B Attentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies have reported the effectiveness of attention in change detection tasks. HPCFNet [28] represents attention as a correlation between feature maps, DR-TA Net [15] evaluates temporal attention by computing the similarity and dependency between a feature map pair, to realize attention-based change detection. CSCDNet [11] employs a correlation filter to compensate for the uncertainty in the nonlinear transformation between live and reference images.…”
Section: B Attentionmentioning
confidence: 99%
“…A major advantage of our proposed approach, owing to its reliance on highlevel contextual attention information rather than low-level visual features, is its potential to operate effectively in test domains with unseen complex backgrounds. In this sense, our approach combines the advantages of two major research directions in the change detection community: pixel-wise differencing [11], [15] and context-based novelty detection [9], [16], by incorporating all available information into the attention mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, changes of the land surface are detected by utilizing the significant data source called multi-temporal remote sensing images in a wide geographical area, and the requirement for conventional field researches is progressively decreased. Here, the most important thing is change detection (CD) and it is described as the detecting operation of changes which is obtained among two or more images that are based on the image properties [5]. The image property's differences such as texture, shape, and value of pixel radiance are can be interconnected to the changes on the ground at various satellite remark times [3].…”
Section: Introductionmentioning
confidence: 99%